Prevalence of Smoking among University Students, Aseer region in Saudi Arabia – A Cross-sectional study - Asma Saad Habbash; Mohanad Qasem A Alshabab; Feras Mohammed R Alqahtani; Raghad Mohammed O Alhussain; Noura A Alshehri; Lizy Sonia Benjamin; Zainab Alqahtani (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Smoking is on the rise among adolescent students which affects public health and well-being. This study was conducted with the aim to estimate the prevalence of smoking among undergraduate students studying at King Khalid University, Aseer, Saudi Arabia.Methods and materials: A cross-sectional study was conducted among 1160 undergraduate male and female students studying at King Khalid University, Saudi Arabia. The data was collected from June to November 2022. A stratified random sampling technique was used to select the samples. The data was collected through a self-administered questionnaire. Data were analyzed using SPSS-24.Results: The students aged between 20 and 21 years (30.3%). The key finding of the study was 17% of the university students were current smokers, 5% had the habit of smoking in the past and 78.6% of the students were non-smokers. 64% of them had used regular cigarettes, 27% of them electronic cigarettes and 9% used both regular cigarettes and electronic cigarettes. 42 % started smoking between 21-25 years of their age. There was a significant association between age and intention to stop smoking with (χ2 = 7.32 at p< 0. 05 levels).Conclusion: Awareness regarding the adverse effects and early prevention of smoking, particularly in young adults, is crucial. Smoking cessation at a younger age is better than treating complications of smoking later in life. Hence this study recommends anti-smoking policies at the University level that need to be started and routinely evaluated.